Improving Environmental Permitting Systems: Integrated Permits in the Netherlands - Hanna Dürtge Tolsma (Central European Public Administration Review)
Environmental law originally developed in a fragmented way (sectoral legislation protecting water, soil or air). This fragmented approach towards environmental protection caused problems. Citizens and businesses applying for a permit are confronted with a range of procedures with a variety of different time limits, assessment criteria and legal remedies. Comparative law research shows that the integration of legislation in the field of environmental law is a growing trend. Policymakers feel the necessity to integrate decision-making in order to optimise the protection of the environment. The first part of this article contains a brief overview of the concept of an integrated process for the granting of environmental permits. The second part discusses the idea of environmental model 4 permit, which has been but forward in the Netherlands. It is questionable if this specific concept of integrated environmental permitting can be achieved within the constraints of Dutch administrative law.